Optical dental whitening efficacy of blue covarine toothpaste in teeth stained by different colors - Oliveira, Morgana [UNESP]; Fernández, Eduardo; Bortolatto, Janaína [UNESP]; Oliveira Junior, Osmir [UNESP]; Bandeca, Matheus; Khajotia, Sharukh; Florez, Fernando (Wiley, 2016)
Objective Evaluate the immediate and cumulative optical whitening efficacy of a blue covarine toothpaste. Materials and Methods 180 bovine tooth specimens with similar shade (ΔE < 3.5) were staining of different beverage: black tea(BT), green tea (GT), red wine (RW), orange soda (OS), and brazilian açai juice (AJ), and then submitted to tooth brushing with a blue covarine toothpaste (Op) or a control abrasive toothpaste (Ab). The whitening effect was evaluated at baseline (B), after staining (S), after 1 day (1D) and 7 days of cumulative use of toothpastes (7D). The color shade chances were assessment by Vita Easyshade reflectance spectroscope and the data of CIELab color coordinates (L∗, a∗, and b∗), color difference (ΔE) and the whiteness index optimized (WIO), were analyzed by two-way mixed analysis of variance (ANOVA) for repeated measures and Bonferroni-corrected t-tests (α = 0.05). Results The analysis showed statistically significant differences before and after staining by colored beverages (p < 0.05), but no differences were found due to the action of toothpaste (p > 0.05), in the CIELab coordinates, ΔE and WIO index. Conclusions The use of toothpastes (Op or Ab) reduced the dental staining caused by different colored beverage, but the whitening effect of blue covarine toothpaste could not be confirmed (p > 0.05).